Pengaruh Kualitas Layanan dan Atraksi Wisata terhadap Kepuasan Wisatawan di Batu Parsidangan Siallagan Samosir - Simbolon, Sabam Fernando; Indra Safari; Oman Sukirman (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This research was conducted based on the observation that Batu Parsidangan Siallagan is one of the main tourist destinations in Samosir Regency and consistently attracts many visitors. The site is highly rated on several travel platforms, confirming its strong potential as a cultural tourism icon. However, despite this popularity, some visitors provide negative feedback, particularly regarding inconsistent service quality, attractions that do not fully meet expectations, and inadequate supporting facilities. These conditions encourage further study to analyze tourists’ perceptions of service quality and tourist attractions, as well as their influence on visitor satisfaction. A total of 99 respondents were selected using purposive non-probability sampling to ensure the data collected aligned with the research objectives. Data were gathered using a structured questionnaire tested for validity and reliability, then analyzed through descriptive statistics and inferential methods, including multiple regression, the coefficient of determination, t-test, and F-test. The findings show that service quality and attractions together account for 56.3% of the variation in visitor satisfaction. These results highlight the need to enhance service quality, create more engaging cultural attractions, improve supporting facilities, and provide continuous training for local human resources so that Batu Parsidangan Siallagan can maintain its status as a leading tourist destination.